Cortical Auditory Evoked Potentials in Cognitive Impairment and Their Relevance to Hearing Loss: A Systematic Review Highlighting the Evidence Gap - Gommeren, Hanne; Bosmans, Joyce; Cardon, Emilie; Mertens, Griet; Cras, Patrick; Engelborghs, Sebastiaan; Van Ombergen, Angelique; Gilles, Annick; Lammers, Marc; Van Rompaey, Vincent (Frontiers in Neuroscience, 2021)
Abstract Background: Alzheimer’s disease (AD) is the most prevalent cause of dementia which affects a growing number of people worldwide. Early identification of people at risk to develop AD should be prioritized. Hearing loss is considered an independent modifiable risk factor for accelerated cognitive decline and dementia in older adults. The main outcome of interest of this review is the alteration of Cortical Auditory Evoked Potential (CAEP) morphology in an AD or mild cognitive impairment (MCI) population with and without hearing loss. Methods: Two investigators independently and systematically searched publications regarding auditory processing on a cortical level in people with cognitive impairment (MCI or AD) with and without hearing loss. Only articles which mentioned at least one auditory elicited event-related potential (ERP) component and that were written in English or Dutch were included. Animal studies were excluded. No restrictions were imposed regarding publication date. The reference list of potential sources were screened for additional articles. Results: This systematic review found no eligible articles that met all inclusion criteria. Therefore, no results were included, resulting in an empty systematic review. Conclusions: In general, dysfunction – being either from cognitive or auditory origin – reduces CAEP amplitudes and prolongs latencies. Therefore, CAEPs may be a prognostic indicator in the early stages of cognitive decline. However, it remains unclear which CAEP component alteration is due to cognitive impairment, and which is due to hearing loss (er even both). In addition, vestibular dysfunction - associated with hearing loss, cognitive impairment and AD - may also alter CAEP responses. Further CAEP studies are warranted, integrating cognitive, hearing, and vestibular evaluations.